Single‐agent ibrutinib versus chemoimmunotherapy regimens for treatment‐naïve patients with chronic lymphocytic leukemia: A cross‐trial comparison of phase 3 studies. Issue 11 (9th October 2018) - Robak, Tadeusz; Burger, Jan A.; Tedeschi, Alessandra; Barr, Paul M.; Owen, Carolyn; Bairey, Osnat; Hillmen, Peter; Simpson, David; Grosicki, Sebastian; Devereux, Stephen; McCarthy, Helen; Coutre, Steven E.; et al.
Abstract: Chemoimmunotherapy (CIT) and targeted therapy with single‐agent ibrutinib are both recommended first‐line treatments for chronic lymphocytic leukemia (CLL), although their outcomes have not been directly compared. Using ibrutinib data from the RESONATE‐2 (PCYC‐1115/1116) study conducted in patients ≥65 years without del(17p), we performed a cross‐trial comparison with CIT data from published phase 3 studies in first‐line treatment of CLL. Progression‐free survival (PFS), overall survival (OS), and safety data for ibrutinib (median follow‐up 35.7 months) were evaluated alongside available CIT data. CIT regimens included: fludarabine + cyclophosphamide + rituximab (CLL8, CLL10), bendamustine + rituximab (CLL10), obinutuzumab + chlorambucil and rituximab + chlorambucil (CLL11), and ofatumumab + chlorambucil (COMPLEMENT‐1). Median age across studies was 61‐74 years, with older populations receiving ibrutinib, obinutuzumab + chlorambucil, or rituximab + chlorambucil. Median follow‐up varied across studies/regimens (range 14.5‐37.4 months). Among all patients, PFS appeared longer with ibrutinib relative to CIT and OS appeared comparable. Relative to CIT studies that similarly excluded patients with del(17p) (CLL10) or enrolled older/less‐fit patients (CLL11), PFS appeared favorable for ibrutinib in high‐risk subgroups, including advanced disease, bulky lymph nodes, unmutated IGHV status, and presence of del(11q). Grade ≥ 3 infections ranged from 9% (ofatumumab + chlorambucil) to 40% (fludarabine + cyclophosphamide + rituximab), and was 25% with ibrutinib. Grade ≥ 3 neutropenia was 12% for ibrutinib and 26%‐84% for CIT. Although definitive conclusions cannot be made due to inherent limitations of cross‐trial comparisons, this report suggests that ibrutinib has a favorable benefit/risk profile and may potentially eliminate the need for chemotherapy in some patients. Randomized, comparative studies are needed to support these findings.